2016
DOI: 10.1016/j.acap.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Parental Predictions and Perceptions Regarding Long-Term Childhood Obesity-Related Health Risks

Abstract: Objectives To assess how parents perceive long-term risks for developing obesity-related chronic health conditions. Methods A web-based nationally representative survey was administered to 502 U.S. parents with a 5–12 year old child. Parents reported whether their child was most likely to be at a healthy weight or overweight, and the probability that their child would develop hypertension, heart disease, depression, or type 2 diabetes in adulthood. Responses of parents of children with overweight and obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 37 publications
1
20
1
Order By: Relevance
“…In total, 15.4% percent of parents said that hypertension was a risk factor, while 11.2% said that heart disease was a risk factor. In addition, compared to the parents of normal weight children, more parents of obese children believed that their children had a high risk of obesity-related health problems (31). These findings reinforce the need to include parents and children in screening programs for risk factors related to excess body weight (31).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In total, 15.4% percent of parents said that hypertension was a risk factor, while 11.2% said that heart disease was a risk factor. In addition, compared to the parents of normal weight children, more parents of obese children believed that their children had a high risk of obesity-related health problems (31). These findings reinforce the need to include parents and children in screening programs for risk factors related to excess body weight (31).…”
Section: Resultsmentioning
confidence: 72%
“…In addition, compared to the parents of normal weight children, more parents of obese children believed that their children had a high risk of obesity-related health problems (31). These findings reinforce the need to include parents and children in screening programs for risk factors related to excess body weight (31). According to Lavie and cols., studies that evaluate the impact of weight loss on the control of cardiovascular disease are extremely important; these studies help with prevention and have a good cost-benefit ratio.…”
Section: Resultsmentioning
confidence: 90%
“…Although parents of youth with chronic conditions tended to show more concern for the weight status of their youth compared with parents of youth without chronic conditions, in general, parental concern was low. This may be problematic, as parents without concern for their child's overweight status may neglect opportunities to mitigate unhealthy weight gain .21 Because of the potentially deleterious physical, social and emotional health effects of overweight and obesity during youth, health care professionals should seek to better engage parents in conversations about childhood obesity‐related health risks and provide strategies to enhance the parents' support for their child's weight management behaviors …”
Section: Discussionmentioning
confidence: 99%
“…21 Because of the potentially deleterious physical, social and emotional health effects of overweight and obesity during youth, health care professionals should seek to better engage parents in conversations about childhood obesity-related health risks and provide strategies to enhance the parents' support for their child's weight management behaviors. 37 This analysis benefits from a number of strengths, including the use of a nationally representative sample of youth with chronic conditions, and the comparison group of youth without chronic conditions. Despite these strengths, findings should be interpreted considering certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study showed that some parents perceived walking and/or running are protective factors against childhood obesity 26 . Finally, one study reported parents' perception regarding to health concerns of childhood obesity, thus parents of obese children are more likely to perceived the risk of hypertension (OR = 1.9), heart disease (OR = 2.26), type 2 diabetes (OR = 2.2) and depression (OR= 1.8) relative to parents of healthy weight children 16 .…”
Section: Parents' Perception Regarding Risk Factors and Health Concermentioning
confidence: 99%